The Effect of Expressive Writing Therapy on Reducing Stress Levels in Chronic Kidney Disease Patients Undergoing Hemodialysis at Undata Hospital - Unggun Cahya Jalu Putra, Windu; Yulianti, Sri; Reza, Moh (Journal of Health and Nutrition Research, 2023)
Chronic kidney disease is a world health problem with a high incidence and prevalence. Someone who suffers from chronic kidney disease must undergo hemodialysis regularly; it causes psychological disorders, including stress. Expressive writing therapy is a psychological therapy that can reduce stress levels by writing to reflect thoughts and feelings. This study aimed to prove the difference in stress levels in patients with chronic kidney disease undergoing hemodialysis at Undata General Hospital before and after being given expressive writing therapy. This type of research was Quantitative with a Pre-experimental design using the One Group Pre Test And Post Test Design. The population in this study amounted to 87 people and a sample of 10 people with a purposive sampling technique. The research results from 10 respondents using the Paired sample t-test obtained a p = 0.000 (p ≤ 0.05). Respondents' stress levels before doing expressive writing therapy were severe stress (30%), moderate stress (40%), and mild stress (30%). Meanwhile, the stress level of the respondents after doing expressive writing therapy was normal stress (50%), moderate stress (20%), and mild stress (30%). In conclusion, expressive writing therapy has an effect on reducing stress levels in patients with chronic kidney disease undergoing hemodialysis at Undata Hospital. It is suggested that the results of this study are expected to be used as material and input for non-pharmacological interventions in reducing stress